2011
DOI: 10.1074/jbc.m111.305235
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Drug Resistance

Abstract: Background: Mycophenolic acid sensitivity varies by 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This suggests that in Cryptococcus IMPDH, MPA binds to additional enzyme forms such as free enzyme or E -IMP. Such a scenario is also found in MPA-resistant Penicillium brevicompactum IMPDH, where the initial hydride transfer step (as opposed to the subsequent hydrolysis step) is either partially or completely rate-limiting, resulting in the predominate enzyme form being E -IMP-NAD + instead of E -XMP*, conferring MPA resistance [46] .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This suggests that in Cryptococcus IMPDH, MPA binds to additional enzyme forms such as free enzyme or E -IMP. Such a scenario is also found in MPA-resistant Penicillium brevicompactum IMPDH, where the initial hydride transfer step (as opposed to the subsequent hydrolysis step) is either partially or completely rate-limiting, resulting in the predominate enzyme form being E -IMP-NAD + instead of E -XMP*, conferring MPA resistance [46] .…”
Section: Resultsmentioning
confidence: 91%
“…Recent work also demonstrates that if the initial hydride transfer step becomes rate-limiting, this reduces accumulation of the enzyme-substrate covalent complex and thus reduces susceptibility to MPA inhibition. Notably, this has occurred in MPA-resistant Penicillium brevicompactum IMPDH without significant residue changes around the substrate/cofactor binding sites [46] , [58] . Our work demonstrates that MPA binds to additional cryptococcal IMPDH forms (an uncompetitive inhibitor should bind only to the enzyme-substrate covalent complex), suggesting the enzyme to be fundamentally functionally different from the human isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that a single residue showed mycophenolic acid resistance, although the binding sites were identical [65]. The kinetic mechanism was controlled for the mycophenolic acid resistance of PbIMPDH-A and PbIMPDH-B [66]. These studies showed that virtual screening by simple prediction is fast and low cost, although experimental verification is needed.…”
Section: Inhibitory Assay Against Clas Impdh∆98-201 Activitymentioning
confidence: 88%
“…The biosynthetic cluster of MPA revealed an additional copy of IMPDH (Fig. 1A), which is insensitive to MPA, thus conferring resistance (1315). Another example is fellutamide B, a proteasome inhibitor produced by Aspergillus nidulans.…”
Section: Introductionmentioning
confidence: 99%